ANALISIS DAMPAK PENGGUNAAN MATERIAL KOMPOSIT RINGAN PADA EFISIENSI BAHAN BAKAR MESIN KENDARAAN BERMOTOR - Herlambang, Herlan; Dwiputra, Andika; Ginggerium Sagala, Akbar (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
The increasing number of motor vehicles globally, especially in developing countries, has created the urgent need to improve fuel efficiency and reduce carbon emissions. Innovations in automotive technologies, including the use of lightweight composite materials like carbon fiber and natural fibers, help reduce vehicle weight and enhance fuel efficiency. While tighter regulations and growing consumer awareness are driving the demand for more eco-friendly vehicles, challenges such as higher production costs and recycling difficulties persist. This study examines the impact of lightweight composite materials on fuel efficiency and emission reduction, providing insights for automotive manufacturers, policymakers, and consumers.